QUASISTATIONARY MODEL OF THE GEOCHEMICAL CYCLE AND EVOLUTION OF THE BIOSPHERE AT THE PRECAMBRIAN-PHANEROZOIC BOUNDARY - Sochava A.V. (My University, 1992)
The Vendian period, which preceded the Phanerozoic, was characterised not only by prominent evolutionary events, but also by an unusual composition of the sulphur, carbon and strontium in the sediments. From the point of view of the proposed model this indicates a significant drop in the content of O2 in the atmosphere and the hydrosphere. This change in the characteristics of the external environment promoted the first appearance of specialised respiratory organs in multi-celled animals. The increase in the content of O2 in the atmosphere following the Vendian-Cambrian boundary served as a precondition for the appearance of exoskeletons in animals and their rapid taxonomic radiation.
Keywords: Precambrian; Precambrian; Докембрий